Functional and Semantic Analysis of Hyperbole as a Literary Expressive Device - Azimova , Muhayyo (The Lingua Spectrum, 2025)
This article analyzes the stylistic functions of hyperbole in artistic texts in English and Uzbek, focusing on its expressive, emotional, and cultural roles. Hyperbole, as an artistic form of exaggeration, enhances the imagery of a text. The study conducts a comparative linguistic-stylistic and linguocultural analysis of hyperbole examples drawn from the works of English and Uzbek authors. Additionally, the role and challenges of translating such stylistic devices are explored. The research thoroughly examines the theoretical foundations of hyperbole, its origins, historical development, and semantic and stylistic characteristics. Particular attention is paid to the communicative-pragmatic functions of hyperbole in discourse, its linguocultural aspects, translation difficulties, and its interactions with other stylistic devices. Examples from English literature, including works by Shakespeare, Dickens, Twain, and Rowling, illustrate hyperbole’s dramatic, satirical, and aesthetic functions. In Uzbek literature, texts by Navoi, Qodiriy, and Vohidov demonstrate hyperbole’s role in creating poetic imagery, intensifying emotional impact, and reinforcing cultural-aesthetic expression through vivid examples.